2016
DOI: 10.1021/acs.langmuir.6b01574
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Moieties Increase the Interaction of Amphiphilic Block Copolymers with Lipid Monolayers

Abstract: The interaction of amphiphilic and triphilic block copolymers with lipid monolayers has been studied. Amphiphilic triblock copolymer PGMA20-PPO34-PGMA20 (GP) is composed of a hydrophobic poly(propylene oxide) (PPO) middle block that is flanked by two hydrophilic poly(glycerol monomethacrylate) (PGMA) side blocks. The attachment of a perfluoro-n-nonyl residue (F9) to either end of GP yields a triphilic polymer with the sequence F9-PGMA20-PPO34-PGMA20-F9 (F-GP). The F9 chains are fluorophilic, i.e., they have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Furthermore, when a hydrophilic–lipophilic polymer is supplied with a third structural element, it expands the possibilities for the development of self-assembled multi-compartment macromolecules [92,93,94,95,96,97,98,99,100,101,102,103,104]. It often has remarkable effects on the catalytic behavior [92,105,106], the interaction with biological membranes [107,108,109,110], or the transport of active substances [103,109,111,112].…”
Section: From Polymer Amphiphilicity To Polyphilicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when a hydrophilic–lipophilic polymer is supplied with a third structural element, it expands the possibilities for the development of self-assembled multi-compartment macromolecules [92,93,94,95,96,97,98,99,100,101,102,103,104]. It often has remarkable effects on the catalytic behavior [92,105,106], the interaction with biological membranes [107,108,109,110], or the transport of active substances [103,109,111,112].…”
Section: From Polymer Amphiphilicity To Polyphilicitymentioning
confidence: 99%
“…Monolayer investigations of the shorter polymer with (PGMA 24 ) at the air–water interface and analysis of the interaction of lipid monolayers with the triphilic and amphiphilic (without fluorinated part) block copolymers were performed. It is concluded that the fluorinated segments located at the polymer end in the triphilic polymer significantly inhibit its removal from the lipid layer, compared to amphiphilic molecules [108].…”
Section: From Polymer Amphiphilicity To Polyphilicitymentioning
confidence: 99%
“…The polybetaine generating the smaller expansion of the monolayer was also the one showing the least cytotoxicity on human breast carcinoma cell MCF7. Schwieger et al [163] used monolayers made of different types of lipids, changing the nature of the polar heads or of the chains, to investigate the interactions between the lipids and two types of PGMA-PPO-PGMA triblock copolymers, one presenting fluorinated end chains. They showed that the fluorinated polymer incorporated more strongly in the monolayer than the non-fluorinated one.…”
Section: Interactions With Model Membranesmentioning
confidence: 99%
“…The replacement of poly(ethylene oxide) block in these polymers by poly(glycerol monomethyl methacrylate) gives rise to a new type of polymers, which have greater ability to interact with membranes compared to poloxamers [18,26,27,28,29]. The polymer retention in membranes is further enhanced upon end capping of the amphiphilic triblock copolymers with perfluorinated moieties [30,31,32]. The resulting macromolecules are polyphilic, simply because their perfluorinated segments are hydrophobic as well as lipophobic [33].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the significance of polymers bearing such components, it is vital to study the interactions of these polymers with biological membranes or their simplified mimics [18]. The interactions between block copolymers and membrane lipids, including DPPC are affected upon α,ω perfluoroalkylation of block copolymers [31,32]. There is a solitary study available in literature on the effect of human serum albumin on F-DPPC monolayers [47], however the effect of polymers on monolayers or bilayers of F-DPPC has never been reported.…”
Section: Introductionmentioning
confidence: 99%